استخدام البرمجة الخطية في تقدير كلفة حركية أفراد موظفي الجماعات المحلية إشارة إلى حالة بلدية بوراشد ولاية عين الدفلى للفترة ( 2022 - 2025 ): The use of linear programming in estimating the cost of mobility of local community employees, referring to the case of the municipality of Bourashid (Ain Defla governorate) for the period (2022-2025) - سعيد منصور فؤاد,; عبد القادر خداوي مصطفى, (Journal of North African Economies, 2025)
The municipality determines its human resource needs with its various competencies, based on assessing the capacity of the available human resource structure and carrying out an objective analysis of performance requirements and conditions inside and outside the institution, for the purpose of reaching the targeted outputs. The purpose of this research is to try to build a model with linear programming to reduce the costs of a predictive plan for the period (2022-2025), related to the mobility of the employees of the municipality of Bourashid (Ain Defla state), and then use the same model to adapt the costs of salaries of the employees included in the plan, as well as the costs of their movement and layoffs to reduce Of the number of laid-offs on the horizon of the plan under study